Staffing the Hospitals : An Urgent National Need - Great Britain. Ministry of Labour and National Service. (London : Published for the Minister of health, the Secrerary of State for Scotland and the Minister of labour and national service by H.M.S.O., 1945)
1945 1945 1940s 20 pages 17 12. Recreation and Social Life. — Hospital domestic workers will naturally wish to participate in social activities outside the hospital. Everything possible should be done to facilitate such participation and where, as will sometimes be the case, local conditions make the development of outside interests a matter of difficulty, every opportunity should be provided for the organisation by the domestic staff of recreation within the hospital. For hospitals or sanatoria in isolated areas provision of adequate recreational facilities inside the hospital is especially important as well as the provision of reasonable transport facilities to enable the staff to pay regular visits to neighbouring towns. Where public transport is inadequate and cannot be improved, the hospital authorities should as soon as possible acquire a vehicle or vehicles of their own for the use of the staff. The Health Departments and Ministry of Labour and National Service will gladly do what is possible to help authorities to secure improvement in transport facilities. 13. Personnel Management. — The control and supervision of domestic staff should, wherever the numbers justify it, be assigned to an officer who has specialised in this work and who will not usually be a trained nurse. This officer should work in consultation with, but not necessarily under the control of, the matron and should have access to the appropriate hospital committee. 14. Methods of Work and Labour Saving Devices. — Special consideration should be given in each hospital to the way in which domestic work is carried out and the full use of labour-saving devices should be encouraged. The Health Departments are appointing specialist officers whose services will be placed at the disposal of any hospital needing advice on this matter. 15. Training and Promotion Prospects. — Hospital domestic employment should be placed on a comparable footing with other services in that it should offer suitable training and prospects of advancement. Workers should be given experience, as far as possible, in the various phases of hospital domestic work, in the kitchens, laundries, workrooms and store rooms, etc. and opportunities of taking up the work which most appeals to them. There should be opportunities for promotion within the hospital and possibilities of upgrading. Small hospitals where there are not adequate facilities for promotion within the institution should seek to combine with other hospitals in order to secure better avenues of promotion for their qualified staff. The Ministry of Labour and National Service would welcome the organisation of training schemes in the larger hospitals, particularly where such hospitals are ready to provide a training field for staff for the smaller hospitals in the same area. The Ministry would be ready to co-operate in the organisation of such schemes and would give financial assistance in appropriate cases in connection with the training of persons released from war-time service. Every facility should be given to domestic workers who are suitable and who so wish to enter for nursing training. 16. Juvenile Workers. — If the hospital service is to recruit an efficient staff it must offer attractions to young people. Hospitals should, therefore, provide training schemes and offer promotion prospects which will attract school leavers. It is, of course, important that girls under 18 should not be brought into contact with patients in circumstances which may be embarrassing or distressing. 17. Uniform. — As soon as circumstances permit, domestic workers should be provided with well-cut uniform for indoor wear or with attractive overalls. 126/TG/RES/X/1036A/4